Dampak Alih Fungsi Lahan Pertanian di Kawasan Objek Wisata Latimojong Terhadap Pendapatan Petani - Abd Rahim; Edy Kurniawan; Pratiwi MK; Putriani (Jurnal Galung Tropika, 2024)
Uncontrolled conversion of agricultural land remains a serious problem in agricultural development, not only in urban areas but also in rural areas. The conversion of agricultural land often impacts the socio-economic life of farmers, especially income. One form of agricultural land conversion currently widely practiced is converting agricultural land into tourist sites. This research aims to determine the impact of the existence of the Civil Camp Karangan tourist attraction on the income of farmers who change land functions. The method used in this research is quantitative descriptive analysis. The Paired sample T-test analysis was used to determine the difference in farmers' income before and after the conversion of agricultural land. The results showed a calculated T value of 7,000> 2.57 T table value. It showed a difference in farmers' income before and after converting agricultural land into a tourist attraction. Thus, efforts are needed to improve the quality of the Civil Camp Karangan tourist attraction so that it still has economic benefits for the community around the location, especially farmers.